Biopharmaceutics and pharmacokinetics of the macrolide antibiotic Josamycin - Skinner, Michael Fredrick (Rhodes University, Faculty of Pharmacy, Pharmacy, 1992)
The investigations detailed herein have been conducted to address various aspects of the biopharmaceutics and pharmacokinetics of josamycin which to-date, have received little or no attention in the literature. Areas of investigation have included the selective determination of josamycin in serum and urine samples, the stability of josamycin in stored biological samples, intrinsic dissolution rates, solubility, acid and alkali stability and bioavailability and pharmacokinetics after dosing with a solution, powder and tablets. High performance liquid chromatography (HPLC) was used as the main analytical tool throughout these studies and proved to be highly versatile for the determination of josamycin in a number of different media. HPLC analysis afforded simple yet accurate determination of josamycin in samples from dissolution, solubility, tablet content and stability studies. Furthermore, the specificity afforded by HPLC was particularly useful for the separation of josamycin from degradation products formed in acid and alkali media. Since metabolites of josamycin are microbiologically active, microbiological assays do not determine the concentration solely of josamycin. An analytical method capable of the selective determination of josamycin in serum and urine samples is therefore required for the procurement of reliable bioavailability and pharmacokinetic data. HPLC affords this selectivity and a method for the selective determination of josamycin in serum and urine was successfully developed. The assay was simple yet precise, accurate and sensitive. Furthermore, it was well suited to the determination of josamycin in a large number of biological samples. Its success was largely due to the use of a solid phase extraction step using Câ‚ â‚ˆ extraction columns, with a highly specific wash sequence followed by a phase separation step after elution from the extraction column. Chromatography was performed on a Câ‚ â‚ˆ reversed-phase analytical column with UV detection of josamycin and internal standard at 231 nm and at 204 nm respectively using a programmable multi-wavelength detector. Only slight modification of the assay described should enable the selective determination of the metabolites of josamycin. This assay, therefore, lays the groundwork for future investigations into the pharmacokinetics of these metabolites. The re-usability of extraction columns was assessed in an attempt to reduce the cost of sample analysis. It was found that extraction columns could be used twice for the extraction of serum samples and up to four times for the extraction of urine samples. The difference between the re-usability of extraction columns for serum and urine samples was ascribed to various differences in the composition of the sample matrix. The stability of josamycin in stored serum and urine samples was also assessed.
Keywords: Antibiotics -- Bioavailability; Antibiotics -- Pharmacokinetics